Dimensi Sosial Dan Regulasi Fiskal: Studi Kualitatif Tentang Perpajakan Di Yayasan Sosial - Antonius Anton; Khristina Yunita; Nina Febriana Dosinta (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to explore how the management of social foundations serving children with physical disabilities understand and manage their tax obligations, as well as how tax compliance contributes to organizational accountability and legitimacy. This research employs a qualitative approach through in-depth interviews, documentation, and non-participant observation to gain a comprehensive understanding of the experiences and practices of foundation managers in responding to fiscal demands. The findings show that the managers’ understanding of taxation remains limited and does not fully cover the technical aspects required for withholding, depositing, and reporting taxes. Limited human resources, manual administrative systems, and the lack of training create challenges that slow down the compliance process. The study also identifies a dilemma between fulfilling social service needs and meeting fiscal obligations due to budget constraints and administrative capacity. Nevertheless, tax compliance enhances accountability and strengthens public trust in the foundation. The study concludes that tax compliance is not only a formal requirement but also an essential component of good governance and organizational legitimacy. The implications suggest the need for improved tax literacy, the development of stronger administrative systems, and continuous technical support to enable foundations to meet their fiscal responsibilities more effectively and sustainably.